Optical Force on a Metal Nanorod Exerted by a Photonic Jet; Nanomaterials; Vol. 12, iss. 2 - Wei Bojian; Gong Shuhong; Li Renxian; Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich; Lin Leke (2022, 2022)
Title screen